2012
DOI: 10.1099/vir.0.039479-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of the Wyeomyia group of orthobunyaviruses and their phylogenetic relationships

Abstract: Phylogenetic analyses can give new insights into the evolutionary history of viruses, especially of viruses with segmented genomes. However, sequence information for many viral families or genera is still limited and phylogenies based on single or short genome fragments can be misleading. We report the first genetic analysis of all three genome segments of Wyeomyia group viruses Wyeomyia, Taiassui, Macaua, Sororoca, Anhembi and Cachoeira Porteira (BeAr328208) in the genus Orthobunyavirus of the family Bunyavir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 62 publications
(83 reference statements)
2
32
0
1
Order By: Relevance
“…30,46,47 Reassortment is a common mechanism described for orthobunyaviruses of the Bunyamwera, Wyeomyia, and Simbu serogroups. 15,[47][48][49] In the case of INHRR 17a-10 virus, we used extensive and robust analyses for testing the possibility of genetic reassortment of the isolate, including matrix of evolutionary distance, phylogenetic reconstructions, and Simplot method. Phylogenetic analyses indicated distinct origins for the S, M, and LRNA segments; the S and LRNAs were related to OROV, whereas the MRNA was related to MDDV (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…30,46,47 Reassortment is a common mechanism described for orthobunyaviruses of the Bunyamwera, Wyeomyia, and Simbu serogroups. 15,[47][48][49] In the case of INHRR 17a-10 virus, we used extensive and robust analyses for testing the possibility of genetic reassortment of the isolate, including matrix of evolutionary distance, phylogenetic reconstructions, and Simplot method. Phylogenetic analyses indicated distinct origins for the S, M, and LRNA segments; the S and LRNAs were related to OROV, whereas the MRNA was related to MDDV (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate the occurrence of M segment reassortment in Potosi and Main Drain viruses and suggest that natural genome reassortment is a driving force in the evolution of viruses of the Bunyamwera serogroup. Further genetic analyses, focusing on other bunyaviruses, showed that the three genome segments of Wyeomyia group viruses (Wyeomyia, Taiassui, Macaua, Sororoca, Anhembi, Cachoeira Porteira, Tucunduba and Iaco viruses) showed that these viruses differ from other viruses in the Bunyamwera serogroup and from other orthobunyaviruses by having truncated NSs sequences that may not counteract the host's interferon response (Chowdhary et al, 2012). Additional findings suggest the occurrence of genome reassortment within the Wyeomyia group, identifying Macaua and Tucunduba viruses as M-segment reassortants that, in the case of Tucunduba virus, may have altered pathogenicity.…”
Section: Reassortment Among Bunyamwera Serogroup Virusesmentioning
confidence: 99%
“…Another group of viruses within the genus Orthobunyavirus, the Wyeomyia group viruses, have truncated NSs sequences that may not code for functional proteins (81). However, antibodies were detected in humans, and the viruses are associated with febrile illness (52,82,83).…”
Section: Discussionmentioning
confidence: 99%